Experimenting with non-fiction VR storytelling: micronarrative, abstraction and interactive navigation. The case of In Pieces VR. Issue 4 (2nd October 2022) - Soler-Adillon, Joan
ABSTRACT: This article presents In Pieces VR, a VR-based artwork and experimental documentary on political prison, and discusses its main design challenges, goals, and creative approach. This project aims at creating a documentary and artistic experience that departs from conventional immersive journalism by presenting to its viewers a story made out of very small narrative units, and with subjects presented in the form of virtual sculptures devoid of any specific identity. The idea is that by leaving much of the making sense left open, viewers will have to fill in the gaps. The working hypothesis is that this will help create a different emotional, intellectual and political connection with the piece than that a conventional documentary would achieve, particularly to an audience unfamiliar with, or even politically alien to its specific context. Public exhibition of the work and user evaluation showed that the piece was successful in creating such connections.